Trehalose enhances neuronal differentiation with VEGF secretion in human iPSC-derived neural stem/progenitor cells - Sean K. Roose; Yoichi Mizukami; Jun Muto; Hideyuki Okano; Masaya Nakamura; Narihito Nagoshi (Regenerative Therapy)
Introduction: Cell transplantation therapy has emerged as a promising approach in regenerative medicine for treating neurological diseases. Neural stem/progenitor cell (NS/PC) transplantation has demonstrated therapeutic efficacy; however, its potential remains limited by suboptimal differentiation and insufficient secretion of pro-healing growth factors. Trehalose, a glucose disaccharide, has been shown to exert neuroprotective effects by inducing autophagy and stabilizing cellular structures. Recent studies suggest that trehalose can modulate growth factor secretion through the CDKN1A/p21 pathway. However, its impact on human induced pluripotent stem cell-derived NS/PCs (hiPSC-NS/PCs) remains unclear. This study investigates the effect of trehalose on neuronal differentiation, cell viability, and growth factor expression in hiPSC-NS/PCs to explore its potential in enhancing transplantation therapy. Methods: hiPSC-NS/PCs were cultured as neurospheres and treated with trehalose (10 mg/ml or 40 mg/ml) for 7 days. Cell viability was assessed using CellTiter Glo® assay. Gene expression analysis was conducted via qRT-PCR and RNA-seq, particularly focusing on CDKN1A, VEGFA, FGF2, and BDNF. Protein expression of SOX2 was analyzed via western blotting. Neurite outgrowth was evaluated using MAP2 immunostaining following differentiation. Statistical significance was set at p < 0.05. Results: Treatment with 10 mg/ml trehalose upregulated CDKN1A expression and promoted neuronal differentiation, as evidenced by reduced SOX2 expression and enhanced neurite outgrowth. RNA-seq analysis revealed the activation of growth factor-related pathways, including VEGFA upregulation, which persisted even after trehalose withdrawal (p = 0.016). However, high concentration (40 mg/ml) significantly reduced cell viability (p = 0.032), suggesting dose-dependent cytotoxicity. Conclusion: Trehalose enhances neuronal differentiation and VEGFA secretion in hiPSC-NS/PCs, potentially augmenting the efficacy of transplantation therapy. These findings suggest that trehalose may serve as a valuable adjunct for neural regeneration, though optimal dosing must be determined to balance differentiation enhancement and cell viability. Further in vivo studies are warranted to validate its clinical applicability.